EFFICACY OF CHITOSAN NANOPARTICLES LOADED 0.7% TETRACYCLINE ON CLINICAL PARAMETERS AND PLATELET-DERIVED GROWTH FACTOR-BB IN RAT MODELS - NASUTION, ERDI EFFENDI; ERVINA, IRMA; AMALIA, MARTINA; AGUSNAR, HARRY; SATRIA, DENNY (International Journal of Applied Pharmaceutics, 2025)
Objective: Tetracycline is a variety of antibiotic therapy for periodontal disease that has been chemically changed to serve as an antibacterial, anti-collagenase, and anti-inflammatory pharmaceutical, decreasing clinical indicators while increasing PDGF-BB healing factor. Chitosan nanoparticles can be used for drug delivery and have qualities such as delayed, sustainable, more absorption, and resilience drug reveal. The aim of the study is to observe the sub-gingival impact of chitosan nanoparticles loaded with 0.7% tetracycline on clinical parameters and PDGF-BB expression by immunohistochemistry observation. Methods: In vivo experimental research with a before-after test control group design. 33 rats were enrolled initially, but only 31 completed the study, two samples perished when the observation was performed. The control group received 0.7% tetracycline once daily for 3 and 8 days, as well as placebo gel once daily for the same period. Clinical parameters and PDGF-BB expression were investigated on baseline, 3rd, and 8th day post-intervention with different trials. Results: The research found that daily tetracycline delivery for 8 d improved clinical measures and raised PDGF-BB expression on 3rd day post-therapy, with significantly analyzed findings (p<0.05). In this study, PDGF-BB expression between all groups after d 3 and 8 wasn’t significantly different (p>0.05). This might be because of the mild severity of periodontitis and shallow pockets in all rat periodontitis model samples. Conclusion: Scaling by applying chitosan nanoparticles loaded with 0.7% tetracycline every day for 8 d improved clinical measures and enhanced PDGF-BB expression on 3rd day. However, PDGF-BB levels on day 8 did not reach statistical significance.